Strengthening Academic Professional Identity with ORCID Codes (Docentes 2.0 Journal, 2024)
In research and academic endeavors, a clear distinction of the activities carried out by each professional is important. This distinction is necessary for the individual recognition of researchers and advancing knowledge. The objective of the present research was to describe the characteristics of knowledge and use of ORCID among professional psychologists in Bolivia. The study used a positive paradigm, quantitative approach, non-experimental design, and a descriptive type. The population was infinite, and a probabilistic sample of 532 professional psychologists in Bolivia was used. Data collection was carried out through an offline survey. The results show that only 35.4% of professional psychologists reported having heard of ORCID, and 56.1% possess this code. The research evidences the need to increase the knowledge and adoption of the ORCID code among professional psychologists in Bolivia. The ORCID code is a valuable tool that can improve visibility, management of academic information, and collaboration among psychology professionals.
Keywords: ORCID; research; psychologists; dissemination of research; professional identity